On the History of the Term ‘Sport’ in the Habsburg Monarchy - Pelc, Martin (Dějiny – teorie – kritika, 2016)
This essay analyses the origins of social reflection of the phenomenon of modern sport against the background of the spread and changes of meaning of the term ‘sport’ in the Habsburg Monarchy, with special emphasis on the Czech environment. The introduction maps the early use of the term. While Austrian historiography of sport places the first appearance of the term to 1841, this study comes with evidence of its use in 1828. The first Czech use of the term in print has been so far traced to 1863. Th e aim of this study is to analyse semantic changes in the term’s meaning in the last third of the nineteenth century, when it shifted from designating the country pursuits and entertainment of the aristocracy (hunting, racing, and horseback riding in general) to a wider range of sports practiced mainly by the urban middle class. The author traces a parallel evolution of the notion of sport in the linguistically Czech and German environment of the Habsburg Monarchy and highlights the shared social background of these changes. In the Czech language, this study identifies several turning points which can be used to define the stages of the term’s use: in 1870, Rieger’s encyclopaedia still presents the traditional definition of the term, in 1882 František Kožíšek in his well-known critical article on the Sokol organisation distinguishes between two kinds of sport, a large and a small one (or high and low), while in the 1890s ‘sport’ is used as a modern collective noun designating the sum of all forms of sport. Th is usage is then adopted and appears in 1905 in the relevant volume of Otto’s encyclopaedia.